0459 Productivity estimation in economic evaluations of occupational health and safety interventions: a systematic review. (21st August 2017) - Steel, Jonas; Godderis, Lode; Luyten, Jeroen
Abstract : Background: OHS interventions increasingly have to demonstrate that they offer good value-for-money. The intervention's effect on productivity gains is thereby essential. However, productivity is not easily measured nor valued, possibly causing employers to underestimate the benefits of OHS programs. Objectives: A systematic review of the measurement and valuation of productivity in economic evaluations of occupational health and safety was conducted, to assess the methodological quality of productivity estimation and the consistency of perspectives used. Methods: Searches were conducted in EMBASE, PUBMED and Cochrane's CENTRAL, between 2007 and December 2016. Two researchers independently reviewed the studies for inclusion. Articles had to be economic evaluations or cost analyses, OHS interventions, aimed at an employed (or return-to-work) population >16 years old and written in English, French, or Dutch. From the included studies, information regarding the general characteristics, inclusion of productivity costs and effects, and methodology of productivity estimation was extracted and analysed. Results: Ninety-two studies were retained. Ninety percent of the studies contrasted intervention costs with absenteeism effects, a third included presenteeism. About half of the studies valued these effects using the human capital approach, twenty-five percent used the friction cost approach. The methodological characteristics were of poor quality in many studies, resulting in a considerable risk of bias. The diversity of studies was also apparent, with studies differing in ten different characteristics concerning the measurement and valuation of productivity. Finally, a new method came into view - direct productivity estimation - that holds a promising alternative to the current standard methods.